ANALISIS KELAYAKAN USAHATANI PADI PETANI TRANSMIGRAN DI KAMPUNG MARGAMULYA DISTRIK SEMANGGA KABUPATEN MERAUKE PROPINSI PAPUA - Ineke Nursih Widyantari; Gerzon Jokomen Maulany; Nila Wijayanti (Universitas Sebelas Maret, 2022)
Margamulya is one of the villages in the Merauke Regency, which is inhabited by many transmigrant farmers from the Javanese ethnic. They introduce rice farming to local residents in Merauke Regency. The purpose of this research is to figure out the received income, output cost, profitability, and feasibility of rice farming in Margamulya Village, Semangga District, Merauke Regency, Papua. The data used in this study are primary data and secondary data. Primary data was obtained from questionnaires and interviews, while the secondary data was obtained from Central Bureau Statistics of Merauke Regency. The results showed rice farming in Margamulya Village, Semangga District, Merauke Regency is feasible to develop with the received profit is IDR.9,864,480, the total cost is IDR.12,176,495, the profitability of 0.81, and R/C value of 1.81.